Hybrid moulds : a case of integration of alternative materials and rapid prototyping for tooling - Pouzada, A. S. (2009)
Hybrid moulds with mouldings blocks made with epoxy composites are being used in injection mouldings of precision parts. In the last decade developments were made in view of applying these production series of thermoplastics injection mouldings. This paper reviews some of the outcomes of research activity on specific issues of manufacturing and utilisation of these tools. Most of the results refer to moulding blocks produced in epoxy composites that were manufactured using the vacuum casting technique. Some references are also made to rapid tooling techniques based on laser sintering.